HAMBATAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI KABUPATEN BIREUEN - Mizwar, Edi; Jarjani Usman; Sri Suyanta (LPPM IAI Almuslim Aceh, 2024)
This research aims to identify the obstacles faced by teachers in implementing the independent curriculum in Bireuen Regency. The approach used in this research is a qualitative approach. The research method employed in this study is a survey method, where information is collected from respondents using a questionnaire through Google Forms. The data collected in this study is sourced from Islamic Education teachers (PAI) at the elementary (SD/MI), junior high (SMP/MTs), and senior high (SMA/MA) levels in Bireuen Regency. The data analysis technique used in this research is a descriptive method. Based on the results of the conducted research, it was found that the obstacles faced by teachers in Bireuen Regency in the implementation of the independent curriculum include a lack of experience with independent learning, limited references, access constraints in teaching, time management, inadequate competencies (skills), mindset changes, insufficient support and training, as well as evaluation and assessment issues